The globalization of inequality - Bourguignon, Francois (Princeton University Press, 2015)
"In The Globalization of Inequality, distinguished economist and policymaker François Bourguignon examines the complex and paradoxical links between a vibrant world economy that has raised the living standard of over half a billion people in emerging nations such as China, India, and Brazil, and the exponentially increasing inequality within countries. Exploring globalization's role in the evolution of inequality, Bourguignon takes an original and truly international approach to the decrease in inequality between nations, the increase in inequality within nations, and the policies that might moderate inequality's negative effects." -- Publisher's description.